Coincidence and fixed point theorems in metric and Banach spaces - Zeqing Liu; Jeong Sheok Ume; Mohammad S. Khan (International Journal of Mathematics and Mathematical Sciences, 2001)
We prove some coincidence and fixed point theorems for generalized (ϕ,f)-contractive type and f-nonexpansive type multivalued and singlevalued mappings in metric and Banach spaces, respectively. Our results extend, improve, and unify a few known results due to Browder, Browder and Petryshyn, Chang, Huang, and Cho, Husain and Latif, Husain and Tarafdar, and Karlovitz.